The Role of Talent Management in Enhancing Employee Engagement in the Digital Era - Syafii, Akhmad; Prahitaningtyas, Sherina; Hidayat, Agus Rohmat (Pusat Publikasi Nusantara, 2025)
This research explores the role of talent management in enhancing employee engagement in the digital era. The study shows that employee engagement is significantly influenced by talent development programs focusing on digital skills, cloud-based technology adoption, and transparent digital leadership. Employees who feel empowered through training and technology support tend to be more engaged in their work, which leads to increased productivity and innovation within organizations. However, challenges remain in terms of technology implementation and the adaptation of digital leadership that need continuous refinement. Therefore, companies should invest more in technology-based talent development programs and strengthen digital leadership to sustain employee engagement. Future research could further explore the impact of talent management in other sectors facing similar challenges.